Carbon (Pergammon Press, 1963)
"Carbon publishes papers that deal with original research on the chemistry, physics and technology of carbonaceous solids consisting essentially of aromatically or tetrahedrally bonded carbon atoms and the materials produced from them. These materials range through chars, activated and pyrolytic carbons (including carbon blacks and soot), graphites, diamond, carbon nanotubes, and the fullerenes."